Perlindungan Hukum Hak-Hak Narapidana Lansia: Studi Kasus Pada Lembaga Pemasyarakatan Kelas II B Sumedang - Mardilana Gautama; Mitro Subroto (Administrative Law and Governance Journal, 2021)
Correctional Institution is a place to conduct training on inmates and correctional students in Indonesia. Before it was known as Penitentiary in Indonesia, it was known as prison. As for the formulation of the problem that the author presents, namely; (1) How the training program is carried out for elderly inmates. (2) Any factors that are inhibited in the application of the rights of elderly inmates in Sumedang Class IIB Penitentiary. This research uses qualitative research methods that use qualitative methods that are descriptive. Data retrieval uses literature study techniques and field studies. This research was conducted at The Sumedang Class IIB Penitentiary located around Sumedang square. The results of research in the field obtained that in lapas accommodate 256 out of a capacity of 100 with a classification of 195 adult inmates, 61 prisoners, 2 female inmates, and 2 elderly inmates. Special treatment is only given to inmates with the elderly category because they already do not have enough ability to perform all activities, as well as the placement of rooms and toilets designed to facilitate them. In addition, spiritual development continues to be carried out and one of the mandatory activities for elderly inmates carried out every day and the separation of residential blocks of elderly inmates is also one of the special treatment given to elderly inmates who do need special treatment and attention.